2010
DOI: 10.1002/ldr.961
|View full text |Cite
|
Sign up to set email alerts
|

Modelling slaking sensitivity to assess the degradation potential of humid tropic soils under intense rainfall

Abstract: In the humid tropics, soil erosion due to the impact of high-intensity tropical rainfall is one of the important environmental problems. A quick assessment of slaking sensitivity of soils that are frequently subjected to the fast wetting of intense rainfall of the humid tropics is necessary for the selection of appropriate soil management practices to avoid soil structure deterioration that results in runoff, seal formation, erosion and eventual degradation. Unfortunately, field and laboratory measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Soil degradation as a result of uncontrolled land use/land cover activities is the leading cause of ecosystem decline, reaching severe levels in certain islands of the Caribbean [71]. The increase in uncontrolled land activities as a result of deforestation, urban sprawl, industrialization and agriculture has undermined the productive capacity of the terrestrial ecosystem [9].…”
Section: Introductionmentioning
confidence: 99%
“…Soil degradation as a result of uncontrolled land use/land cover activities is the leading cause of ecosystem decline, reaching severe levels in certain islands of the Caribbean [71]. The increase in uncontrolled land activities as a result of deforestation, urban sprawl, industrialization and agriculture has undermined the productive capacity of the terrestrial ecosystem [9].…”
Section: Introductionmentioning
confidence: 99%
“…Wuddivira et al [54] showed that River Estate is structurally weak and prone to slaking. Under wetting, this soil quickly loses aggregate stability and collapses, leading to low macroporosity and pore continuity.…”
Section: Redox Potentialmentioning
confidence: 99%
“…Soil-aggregate breakdown under a fast wetting process is often ascribed to the slaking effect. Slaking is a physical process whereby aggregates are disintegrated either by forces exerted by clay swelling during wetting or by compressed air in an aggregate (Zaher & Caron, 2008;Wuddivira et al, 2010). Clay swelling during wetting resulted from surface hydration and an overlap of diffuse double layers (Abu-Sharar et al, 1987).…”
Section: Soil Aggregate Stability Under Different Electrolyte Concentmentioning
confidence: 99%